A Systematic Review on Hypertension Risk Factors in Indonesia - Sri Hidayati (Universitas Islam Negeri Sunan Ampel Surabaya, 2018)
Hypertension has become a global problem because of its prevalence continues to rise to an alarming stage. It was estimated that by the year 2025 about 29% of adults worldwide will suffer from hypertension. The purpose of this research was to identified the hyertension risk factors  occurrence by using systematic review on hypertension-related existing publication and research in Indonesia. From the sixteen studies during the year 1999 untill 2015 and consisted 1 undergraduate paper, 2 theses and 16 research publications, 4 of them was conducted in the year of 2014. The amount of samples studied ranged from 30 up to 657 respondents and all of them were catagorized as primary data. Most of the research used cross sectional and case control design. In terms of literatures utilization, there were 2 to 37 domestic literature has been used while there were only 1 up to 24 international reference has been used for the studies. Several major hypertension risk factors in Indonesia were identified, including age, Body Mass Index and respondents smoking behavior.